Pengaruh Terapi Relaksasi Otot Progresif Dan Murotal Al-Quran Terhadap Kulitas Tidur Pasien Hipertensi Di Desa Betek Kecamatan Krucil Kabupaten Probolinggo - Nuraini Nuraini; Achmad Kusyairi; Iin Aini Isnawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Hypertension is a condition where the systolic pressure is above 140 mmHg, while the diastolic pressure is above 90 mmHg. Some hypertension patients often complain of headache, weakness, fatigue, shortness of breath, restlessness, nausea and vomiting, epistaxis and decreased consciousness. This can cause sleep problems in hypertensive patients. Sleep disorders are a collection of conditions characterized by disturbances in the amount, quality or timing of sleep in an individual. One technique to improve sleep quality is progressive muscle relaxation therapy and murotal Al-Quran.This research method uses Pre-Experimental with one group pre-post test approach. The population is 40 respondents and uses a total sampling (technique).The instrument used was a sleep quality questionnaire, measured by the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI), then data were collected through Editing, Coding, Scoring, and Tabulating processes. The data obtained were analyzed using the Wilcoxon test.The results showed that the average value of sleep quality before progressive muscle relaxation and murotal Al-Quran therapy was performed was 8.30, while after progressive muscle relaxation and murotal Al-Quran the average value of sleep quality was 6.08. The results of the analysis test showed that there was an effect of progressive muscle relaxation therapy and murotal Al-Quran on improving sleep quality of hypertensive patients with -value = 0.000 <α = 0.05. This therapy performs 15 relaxation movements accompanied by the sound of murotal Al-Quran which makes a person relax and calm so that this calmness acts as a pain reliever that makes the patient happy and gives positive energy in a person. this makes the mood to be happy so as to create a good quality sleep. Keywords: Hypertension, sleep quality, progressive muscle relaxation therapy and murotal Al-Quran.